On-chip cell separation and manipulation using traveling wave dielectrophoretic force controlled by four-phase signal generator - Jaruwongrangsee, Kata; Maturos, Thitima; Bunthawin, Sakshin; Wisitsoraat, Anurat; Sangworasil, Manas; Tuantranont, Adisorn (My University, 2011)
In this work, we present a device for cell manipulation and separation using travelling wave dielectophoretic (twDEP) force. The device consists of microchamber and 16 parallel electrode array controlled by four-phase signal. The dielectrophoretic PDMS chamber and Cr/Au parallel electrode array were fabricated by standard microfabrication techniques. The driving signals for the twDEP system are produced by a specially designed four-phase signal generator. The signal generator can be operated in a fixed or±90° phase shift mode with varying frequency, applied voltage and shift interval. In addition, the signal conditions can be store to and retrieved from a built-in database. The twDEP system was tested with polystyrene microspheres suspension in de-ionized water and red blood cells in D-mannitol solution. Cells responded to the electric field in various mechanisms depending on the applied signals conditions. The results showed that the twDEP force occurred when the applied signals were 10 V (50 kHz-700 kHz) and 7V (30 kHz-1MHz) for 4.5 μm and 10 μm microspheres respectively. The mixed solution containing equal amount of 4.5 and 10 μm microspheres were used for separation test. Under the signal conditions for 10 μm microspheres, the microspheres were moved under twDEP force while the smaller microspheres were attached to the electrodes. Therefore, the twDEP device can successfully manipulate and separate the microspheres of different sizes, and it can be further applied for cells selection. © 2011 IEEE.
Keywords: cell separation; Traveling wave dielectrophoresis